The value of ultra-sensitive troponin I in determining the prognosis of patients with the suspected acute coronary syndrome in the emergency department - Unal, Osman Gursoy; Korkut, Mustafa; Unal, Aslihan Yuruktumen; Bedel, Cihan; Unal, Manolya Yildiz (Annals of Medical Research, 2021)
Aim: Acute coronary syndromes (ACS) have significant mortality and morbidity in our country and the world. With the development of technology, early diagnosis and treatment may be possible. Ultra-sensitive troponin I (us-TnI) test developed a few years ago has provided accurate detection of even lower troponin concentrations using a microparticle immunoassay. There are very few studies in the literature about us-TnI showing prognosis. In this study, we aimed to find the value of the newly introduced us-TnI in determining mortality in one-month and three-month follow-ups. Materials and Methods: The study included all patients who were admitted to our tertiary emergency department (ED) between November 2015 and June 2016 and whose us-TnI levels was studied considering ACS. Whether the follow-up of the patients included in the study resulted in death was determined. The patients were classified according to the date of death based on their mortality status at the end of the first month and third month. Results: It was found that of the patients, 4.0% (n=264) died within 1 month after the first troponin measurement, while 6.8% (n=444) died within 3 months after the first troponin measurement. The AUC of the baseline us-TnI value in determining cardiac death at the end of the first month was 0.803 (95% Cl: 0.793-0.813) and the AUC of the baseline us-TnI value in determining cardiac death at the end of the third month was 0.763 (95% Cl: 0.752-0.773). Conclusion: Us-TnI studied at the time of admission to ED is an early indicator of mortality in patients with the diagnosis of ACS.